Impact of Renal Failure on F18-FDG PET/CT Scans - Kode, Vishwajit; Karsch, Holly; Osman, Medhat M.; Muzaffar, Razi (Frontiers in Oncology, 2017)
Objective: The current guidelines for 2-deoxy-2-[18F]fluoro-D-glucose (18F-FDG) PET/CT scanning do not address potential inaccuracies that may arise due to patients with End Stage Renal Disease (ESRD). We report a retrospective analysis of standard uptake values (SUVs) in patients with and without ESRD to identify if these patients require a protocol adjustment. Methods: Patients were matched based on age, gender and BMI which are all potential effectors on observed SUV. Thirty patients were selected with ESRD of which 12 were on dialysis. All 30 patients had age, gender and BMI control matches. In addition, to asses ESRD, BUN and creatinine levels were observed within one month of the scan. PET/CT scans for both the ESRD patients and controls were performed 60 minutes after FDG injection. SUV values were obtained by placing circular regions of interest in the right hepatic lobe (LSUV) and left psoas muscle (PSUV). Results: For the 30 ESRD patients, the mean LSUV was 2.77 and PSUV was 1.43 while the controls had mean LSUV 2.74 and PSUV 1.42. The SUV values from both the liver and psoas muscle were not significantly different between the ESRD patients and the normal controls with p values >0.05. In addition, dialysis and gender also had no effect on SUV values. Conclusion: Our data suggests renal failure patients do not require an adjustment in protocol and the standard protocol times should remain.